2023
DOI: 10.3389/fped.2023.1112812
|View full text |Cite
|
Sign up to set email alerts
|

Early antibiotics and risk for necrotizing enterocolitis in premature infants: A narrative review

Abstract: While prompt initiation of antibiotics at birth due to concerns for early onset sepsis is common, it often leads to many preterm infants being exposed to treatment despite negative blood cultures. Such exposure to early antibiotics can impact the developing gut microbiome putting infants at increased risk of several diseases. Necrotizing enterocolitis (NEC), a devastating inflammatory bowel disease that affects preterm infants, is among the most widely studied neonatal disease that has been linked to early ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 114 publications
1
2
0
Order By: Relevance
“…We have also shown that postnatal supplementation with the probiotic LGG can help ameliorate the negative impact of antibiotics on intestinal proliferation and reduce gut injury. Our findings in mice support accumulating evidence from human studies regarding the increased risk of NEC with peripartum antibiotic exposure [ 18 , 22 , 26 , 72 ]. Our findings also provide supporting evidence that supplementation with probiotics may be an effective strategy to help offset the harmful effects of antibiotics.…”
Section: Discussionsupporting
confidence: 88%
“…We have also shown that postnatal supplementation with the probiotic LGG can help ameliorate the negative impact of antibiotics on intestinal proliferation and reduce gut injury. Our findings in mice support accumulating evidence from human studies regarding the increased risk of NEC with peripartum antibiotic exposure [ 18 , 22 , 26 , 72 ]. Our findings also provide supporting evidence that supplementation with probiotics may be an effective strategy to help offset the harmful effects of antibiotics.…”
Section: Discussionsupporting
confidence: 88%
“…However, in preterm, very low-birthweight infants, each day of antibiotic treatment has been associated with an increased risk of late-onset sepsis, NEC, or death [ 97 ]. Indeed, such exposure to early antibiotics can impact the developing gut microbiome [ 98 ], gastrointestinal transit [ 99 ], stool patterns, and oral feeding tolerance [ 100 , 101 ].…”
Section: Antibiotics and Acid Suppressants Can Impact The Development...mentioning
confidence: 99%
“…Bury and Tudehope performed a systematic review evaluating the benefits and harms of enteral antibiotic prophylaxis for NEC in low birth weight and preterm infants. They found evidence that enteral antibiotics could have a prophylactic effect on the development of NEC but also raised concerns about potential harm, particularly related to the formation of resistant bacteria 187 . Interestingly, in pigs, the beneficial effects against NEC were limited to oral and non-parenteral administration of antibiotics 188–190 .…”
Section: Prevention and Treatment Of Necmentioning
confidence: 99%